Venous thromboembolism in children undergoing surgery: incidence, risk factors and related adverse events. Issue 1 (14th April 2020) - Mets, Elbert Johann; McLynn, Ryan Patrick; Grauer, Jonathan Newman
Abstract : Background: Although less common in adults, venous thromboembolism (VTE) in children is a highly morbid, preventable adverse event. While VTE has been well studied among pediatric hospitalized and trauma patients, limited work has been done to examine postoperative VTE in children undergoing surgery. Methods: Using data from National Surgical Quality Improvement Project Pediatric database (NSQIP-P) from 2012 to 2016, a retrospective cohort analysis was performed to determine the incidence of, and risk factors for, VTE in children undergoing surgery. Additionally, the relationships between VTE and other postoperative adverse outcomes were evaluated. Results: Of 361 384 pediatric surgical patients, 378 (0.10%) were identified as experiencing postoperative VTE. After controlling for patient and surgical factors, we found that American Society of Anesthesiologists (ASA) class of II or greater, aged 16–18 years, non-elective surgery, general surgery (compared with several other surgical specialties), cardiothoracic surgery (compared with general surgery) and longer operative time were significantly associated with VTE in pediatric patients (p<0.001 for each comparison). Furthermore, a majority of adverse events were found to be associated with increased risk of subsequent VTE (p<0.001). Conclusion: In a large pediatric surgical population, an incidence of postoperative VTE of 0.10% was observed. Defined patient and surgical factors, and perioperative adverse events were found to be associated with such VTE events.